Investigating the Effect of Organizational Jealousy with Job Compatibility with the Mediating Role of Organizational Trust and Moderating Quality of Work Life in Diwaniyah Teaching Hospital - Wasan Kamil Afloog (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The objective of this investigation is to investigate the implication of organizational jealousy with occupation compatibility with the mediating duty of organizational assurance and moderating typicality of act living in Diwaniya Teaching Hospital. The investigation manner is applied in Conditions of objective and descriptive and survey in Conditions of conducting manner. The statistical society includes all the occupationholders of Diwaniya Teaching Hospital, whose number is 280, and in instruction to characterize the sample size, Cochran's formula was utilizated, and the number of 162 people was scaled randomly. The manner of collecting inestablishment is aboard the questionnaire tool and to scale organizational jealousy aboard Vecchio (2005) questionnaire, organizational assurance aboard Alonen et al. (2008) questionnaire, occupation compatibility aboard Davis and Lafqvist (1991) questionnaire, typicality of act living aboard Walton (1973) questionnaire. became. After compiling the initial frameact, coefficient analysis was done in instruction to obtain construct accuracy. Cronbach's alpha coefficient was utilizated to scale the relicapability of the questionnaire. Then, all the proposed hypotheses were tested and analyzed using the structural equation figureing technique and using smart pls software, and the findings showed that organizational jealousy with occupation compatibility with the mediating duty of organizational assurance and moderating the typicality of act living in Diwaniya Teaching Hospital has a remarkable implication.